CONCEPT OF COMPETENCE IN THE CIRCULAR ECONOMY IN THE INTERNATIONAL SCIENTIFIC DISCOURSE - Sysoyev, Oleksiy (Educological discourse, 2021)
The article presents an analysis of the concept of “competence in the circular economy” in the international scientific area. This analysis was carried out through the study of foreign scientific literature, in particular, modern reports of educational organizations, projects, guidelines of leading universities and publications on this issue. The components of competence in circular economy are shown, the detailed content of competences in circular economy, the matrix of competences in circular economy consists of five levels of training, comparable to Bloom's taxonomy. The didactic approach to training is given. It is concluded that this is a complex concept, understood in a broader and narrower sense. In a broad, general sense, “competence in the circular economy” includes the components needed to make decisions in complex transition processes, in particular systems thinking, design, and multi-perspective thinking, which are integrated with innovative competencies. In a narrow sense, “competence in a circular economy” includes components specific to a particular professional field.